Metode penelitian kebidanan dan teknik analisis data : contoh aplikasi dan studi kasus / A. Aziz Alimul Hidayat - AZIZ ALIMUL HIDAYAT, A, 1974- (Salemba Medika, 2014)
viii, 212 [44] hlm. : ilus. ; 24 cm [3 eks.]